Pengaruh pH Pada Penentuan Ion Logam Fe3+ Secara Anodic Stripping Voltammetry Menggunakan Pencil Lead Electrode Modifikasi Lapisan Tipis Emas - Akhmad, Ashta Varan; Sari, Trisna Kumala; Ulianas, Alizar; Suryani, Okta (Periodic, 2024)
Fe3+ metal ions have been electrochemically detected using a pencil lead electrode modified with gold thin layer. The modification of the gold thin layer is carried out by sweeping-potential electrodeposition using the cyclic voltammetry method. The purpose of this study was to determine the optimum pH conditions for measuring Fe3+ metal ions using HNO3 as a supporting electrolyte. The pH optimization is carried out using the Anodic Stripping Voltammetry (ASV) method. This technique involves a pre-concentration step where Fe3+ is reduced to Fe0 on the electrode surface in HNO3, followed by a stripping step in ASV where Fe0 is oxidized back to Fe3+. The results showed that HNO3 with pH 1 is the optimum pH for measuring Fe3+ metal ions using Au/PLE electrodes with a test analyte concentration of 250 μM. The anodic peak of the Fe3+ metal ion appears at a potential of 0.55 V.